Validation of the Maxillary Sinus Roof as a Landmark for Navigating the Pediatric Skull Base. (January 2020) - Evans, Sean S.; Banks, Catherine; Richman, Joshua; Woolley, Audie; Cho, Do Yeon; Woodworth, Bradford
Objective: To define a new anatomic relationship in pediatric sinus surgery, assessing the maxillary roof as a constant safe landmark to avoid skull base injury in the pediatric population. Study Design: Retrospective analysis. Setting: Tertiary care children hospital. Subjects and Methods: A retrospective analysis was performed of all computed tomography scans of the sinuses and facial bones at the emergency department of a tertiary children's hospital over the course of a year. Radiographic measurements included the lowest cribriform plate and planum sphenoidale (PS) heights, or posterior skull base when not yet pneumatized, as well as the highest maxillary roof height. The nasal floor was used for reference. Statistics were performed via Shapiro-Wilks test with a P -value of .05 indicating statistical significance. Results: Three hundred and seven unique scans were reviewed (38.9% female; n = 122; P = .58). Age stratification was based on previously described sinus growth patterns. In all patients, the maximum maxillary height was inferior to the lowest measured cribriform lamella and PS ( P < .001; CI, 98.5%-99%). Inter- and intrarater reliability and accuracy were verified through blinded review and re-review (ρ = .99 and .98 respectively, P ≤ .001). The validity of sole coronal measurements due to incomplete sagittal reformatting was also confirmed (ρ = 1.00, P ≤ .001). Conclusion: Despite variation in sinus growth and development in children, the current study demonstrated the validity of the maxillary sinus roof as a constant safe landmark in the pediatric population, offering a novel anatomic relationship for teaching safety in performing pediatric sinus surgery. Level of Evidence: 4